The Effect of Competition Sounds on Balance Performance in Football Players - Tekin, Ebru; Egesoy, Halit; Unver, Fatma (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2024)
Objective This study aimed to investigate the impact of competition environment sounds on the static and dynamic balance of football players.Materials and Methods Thirty-two football players with a mean age of 21.12±2.99 years and a body mass index of 21.98±2.58 kg/m² were included in this study. The initial assessment condition (whether in a quiet environment or with competition sounds) was determined by simple randomization. Forty-eight hours later, at the same time of day, the tests were repeated with the environmental conditions reversed. Balance performance was assessed using the Tecnobody device for both static and dynamic balance. Results In the static balance test, it was found that the surface area covered significantly decreased in the environment where competition sounds were played (p=0.014), while there was no significant change in overall sway (p=0.313), anteroposterior sway (p=0.852), or mediolateral sway (p=0.104). In the dynamic balance test, no significant change was observed in anteroposterior sway (p=0.411), but mediolateral sway (p=0.025) and overall sway (p=0.042) significantly decreased. Additionally, there was a significant improvement in the athletes’ score for reaching the target (p=0.003). The perceived difficulty levels during the tests were found to be significantly lower in both the static (p=0.048) and dynamic (p=0.001) balance tests in the environment where competition sounds were played.Conclusion In conclusion, competition environment sounds were found to positively affect the balance performance of football players and reduce the perceived difficulty level. Incorporating balance training with competition sounds during athlete rehabilitation may contribute to improved balance recovery.
Keywords: Sound; Balance; Football; Competition